Human lymphatic vessel contractile activity is inhibited in vitro but not in vivo by the calcium channel blocker nifedipine. (29th September 2014) - Telinius, Niklas; Mohanakumar, Sheyanth; Majgaard, Jens; Kim, Sukhan; Pilegaard, Hans; Pahle, Einar; Nielsen, Jørn; de Leval, Marc; Aalkjaer, Christian; Hjortdal, Vibeke; Boedtkjer, Donna Briggs
<x xml:space="preserve">Abstract</x> Key points We studied the effects of antihypertensive calcium channel blockers on CaV1.2, the predominantly expressed L‐type calcium channel in the largest human lymphatic vessel, the thoracic duct. Human lymphatic collecting vessels, both large and small, are highly‐sensitive in vitro to calcium channel blockers; exposure to these drugs inhibits endogenous lymphatic contractile activity and action potentials and diminishes noradrenaline‐induced phasic contractions. In vivo administration of calcium channel blocker nifedipine to healthy volunteers did not reduce lymphatic contractile activity despite all subjects achieving nifedipine plasma concentrations comparable with those observed to affect contractile function in vitro. These results indicate that calcium channel blocker‐related oedema is unlikely to be exacerbated by an off‐target effect of the drugs diminishing lymphatic pumping and fluid removal. Abstract Calcium channel blockers (CCB) are widely prescribed anti‐hypertensive agents. The commonest side‐effect, peripheral oedema, is attributed to a larger arterial than venous dilatation causing increased fluid filtration. Whether CCB treatment is detrimental to human lymphatic vessel function and thereby exacerbates oedema formation is unknown. We observed that spontaneous lymphatic contractions in isolated human vessels (thoracic duct and mesenteric lymphatics) maintained under isometric conditions were inhibited by therapeutic concentrations (nanomolar) of the CCB nifedipine while higher than therapeutic concentrations of verapamil (micromolar) were necessary to inhibit activity. Nifedipine also inhibited spontaneous action potentials measured by sharp microelectrodes. Furthermore, noradrenaline did not elicit normal increases in lymphatic vessel tone when maximal constriction was reduced to 29.4 ± 4.9% of control in the presence of 20 nmol l−1 nifedipine. Transcripts for the L‐type calcium channel gene CACNA1C were consistently detected from human thoracic duct samples examined and the CaV1.2 protein was localized by immunoreactivity to lymphatic smooth muscle cells. While human lymphatics ex vivo were highly sensitive to nifedipine, this was not apparent in vivo when nifedipine was compared to placebo in a randomized, double‐blinded clinical trial: conversely, lymphatic vessel contraction frequency was increased and refill time was faster despite all subjects achieving target nifedipine plasma concentrations. We conclude that human lymphatic vessels are highly sensitive to nifedipine in vitro but that care must be taken when extrapolating in vitro observations of lymphatic vessel function to the clinical situation, as similar changes in lymphatic function were not evident in our clinical trial comparing nifedipine treatment to placebo.